(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The Brazilian National Commission for Nuclear Energy (CNEN) establishes a reference level of 1000 Bq m-3 of radon concentration in underground mines. Solid State Nuclear Track Detectors – SSNTD is considered the main method of analysis in radon research. The methods and instrumentation used to determine radon concentration needs to be validated by calibration to ensure reliable results. This work aims to determine the calibration factor of CR-39 detectors exposed to well known radon concentrations produced in closed systems by sources of Ra-226 with activities of 3.379 kBq and 0.483 kBq, which are NISTS sources of activities and emanation factors. The detectors were exposed to six different levels of exposure. The conversion factor between tracks density and exposure obtained was K = 52.028 ± 0.752 [(tracks density.cm-2)/(kBq.d.m-3)]. As object of application of this work, mines were chosen with high radon concentrations reported by Santos (2015) in special a pegmatite mine located in the northwest of Minas Gerais. This mine presented radon concentration much higher than the recommended by the Brazilian national standard NN.CNEN.4.01, up to 7384 ± 517 Bq m-3.